Professional Competence of Social-Science Teachers Through an Integrated Literacy Program in Encouraging Students' Interest in Reading - Aqda Al Murobby; Azharotunnafi Azharotunnafi (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2023)
Interest in reading in Indonesia is still relatively low, while reading is a positive action. There are many benefits that we will get through reading, by reading students will add a lot of knowledge. In encouraging students' interest in reading, the role of a professional teacher is needed. This study aims to find out how the professional competence of social studies teachers at SMP N 1 Merakurak in encouraging students' reading interest through an integrated literacy program and the constraints of social studies teachers in encouraging students' reading interest at SMP N 1 Merakurak. The research method used in this research is descriptive qualitative method with data collection techniques through observation, interviews, and documentation. Based on the research results, social studies teachers at SMP N 1 Merakurak have appropriate professional competence. Based on Rusman and Cooper's theory, the role of social studies teachers in encouraging students' interest in reading is through the role of the teacher as teacher, educator, administrator, facilitator, model and role model. Peters and Kunandar. Through an integrated literacy program, the teacher's role is maximized so that it can encourage students' reading interest in social studies subjects at SMP N 1 Merakurak. Integrated literacy is an effort to integrate reading literacy programs with school culture in the form of intra-curricular programs with regular and co-curricular learning with school cultural activities such as religious studies of fiqh and morality, and the tahfid program. In addition, there are teacher obstacles in encouraging students' interest in reading, namely student focus begins to decrease in the middle of learning, students can open applications other than Illustrated PPT, and there are students who do not carry cellphones. The recommendation for school principals is to continue to implement a reading corner but accompanied by assistance from the teacher, while teachers are expected to be able to implement a reward and punishment system in submitting assignments.Key Words: Professional Competence; Teacher's Role; Reading Interest; Integrated Literacy; IPS SubjectsÂ